PENERAPAN MODEL PBL BERBASIS MEDIA SERBANEKA UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN IPAS DI SD NEGERI KETAWANG - Aini, Nur; Kusumaningrum, Diana (Universitas Islam Raden Rahmat Malang, 2024)
Abstract: Based on the results of observations and interviews with teachers and fourth grade students at Ketawang State Elementary School, it can be seen that based on the outline of science learning activities in class, they are still conventional and lack the use of media and learning models, resulting in monotonous learning and low cognitive learning outcomes for students. Based on the initial objective of the study, namely to find out about students' cognitive learning outcomes through the application of various media-based PBL models (pictures, blackboards, worksheets and the surrounding environment). The type of research used is the PTK model of Kurt Lewin (in Yuliandra, 2020) that each cycle has 4 stages. This research was conducted in 2 cycles, each cycle with 2 meetings. Grade IV students as subjects in this study and a total of 30 students. Data collection techniques were tests, observation and documentation. The results showed that students' cognitive learning outcomes increased in cycle I to cycle II by 40% from the results of the percentage of the first cycle of 46.66% while the second cycle was 86.66%. Based on the results of the research above, it can be concluded that the cognitive learning outcomes of fourth grade students at Ketawang State Elementary School in the Science subject on natural resources and human needs have increased through the application of a variety of media-based PBL models. Keywords: PBL, various media, cognitive learning outcomes.